Incidence of Short Term Private Capital Outflow: Empirical Analysis in Nigeria - Olanrewaju, Raji Rahman (The Economics and Finance Letters, 2019)
Over the years, the rising uncertainty in macroeconomic policy environment coupled with the prevailing uncertain non-economic factors like political instability, corruption, poor governance, civic conflicts and property right is perceived to be having contributing factors on short term private capital outflow in Nigeria. The study investigated the incidence of short term private capital outflow in Nigeria where a combination of the push factors and portfolio risk theories were adopted in the study for the period 2013/March – 2018/May using the fully modified OLS technique. The long-run and short-run results show that uncertainty of macroeconomic policy environment such as inflation-price instability, real exchange rate volatility and lack of confidence on domestic stock market enhanced the increasing level of short term private capital outflow in Nigeria. The study recommends that authority should adopt more pro-growth policies that can ensure and maintain sound domestic macroeconomic policies to stem short term private capital outflow and that stock market authority should ensure accountability and transparency to strengthen the interest of domestic investors if they want to reduce the outflow of domestic capital.